Causative Agents of American Tegumentary Leishmaniasis Are Able to Infect 3T3-L1 Adipocytes In Vitro - Mendes, Bruno; Minori, Karen; Consonni, Silvio R.; Andrews, Norma W.; Miguel, Danilo C. (Frontiers in Cellular and Infection Microbiology, 2022)
Although macrophages have long been considered key players in the course of Leishmania infections, other non-professional phagocytes have lately been shown to maintain low levels of the parasite in safe intracellular niches. Recently, it was demonstrated that the adipose tissue is capable of harboring Old World L. (L.) infantum in mice. However, there is no evidence of experimental adipocyte infection with New World Leishmania species so far. In addition, it was not known whether adipocytes would be permissive for formation of the unique, large and communal parasitophorous vacuoles that are typical of L. (L.) amazonensis in macrophages. Here we evaluated the ability of L. (L.) amazonensis and L. (V.) braziliensis promastigotes and amastigotes to infect 3T3-L1 fibroblast-derived adipocytes (3T3-Ad) using light and transmission electron microscopy. Our results indicate that amastigotes and promastigotes of both species were capable of infecting and surviving inside pre- and fully differentiated 3T3-Ad for up to 144 h. Importantly, L. (L.) amazonensis amastigotes resided in large communal parasitophorous vacuoles in pre-adipocytes, which appeared to be compressed between large lipid droplets in mature adipocytes. In parallel, individual L. (V.) braziliensis amastigotes were detected in single vacuoles 144 h post-infection. We conclude that 3T3-Ad may constitute an environment that supports low loads of viable parasites perhaps contributing to parasite maintenance, since amastigotes of both species recovered from these cells differentiated into replicative promastigotes. Our findings shed light on the potential of a new host cell model that can be relevant to the persistence of New World Leishmania species.